Thai engineer ASEAN readiness: A structural equation model analysis - Kraisuth, Duangporn; Panjakajornsak, Vinai (My University, 2017)
At the start of 2016, the 10-member nation of the Association of Southeast Asian Nations (ASEAN) entered a new era. With it, came the decade old start of the implementation of the 2005 mutual recognition arrangement (MRA) on engineering services and the free flow of skilled labor (FFSL). Although noble intentions, actual specifications and qualifications for this movement heavily restrict its actual implementation. This study therefore conducted both a quantitative and qualitative analyse of 412 engineers selected from a population of 1,211 Thai Federation of Industries companies to investigate how need, gap, and competency affect readiness. The structural equation model was conducted with AMOS 21 software and from the analysis, competency (b =0.16) and needs (b =0.77) demonstrated a significant effect on readiness, while needs demonstrated a significant effect on gap. Finally, the research determined that less than 1% were certified as ASEAN engineers, which is a pre-condition for registration for work as an engineer in another ASEAN country, with cultural awareness of other member nations ranked as the weakest link in an engineer’s readiness perception.
Keywords: ACPE; APEC; Competency; FFSL; Gap; MRA; Need; Registered foreign professional engineer